1. Subscriberjoe shmo
    Strange Egg
    podunk, PA
    Joined
    10 Dec '06
    Moves
    7733
    22 Jan '10 03:456 edits
    hello all, stuck on a problem looking for some insight

    A particle travels along the path, y^2 = 4x with a constant speed of V = 4(m/s). determine the x, and y components of the particles velocity and acceleration when the particle is at x = 4(m)

    im going to use prime notation for ease of formatting

    heres where im at so far

    a particles velocity is tangent to its path so I need to find the slope of the function at the given x

    y^2 = 4x
    2y*y'(x) = 4

    y'(x) = 2/(y)
    y'(4) = 1/2

    from here I can find Vx,and Vy (the x-y components of the velocity respectivley)
    from the right triangle (2,1,Sqrt(5))

    @x=4......{y'(t) =Vy = ||V||*1/sqrt(5) = 4/sqrt(5)
    ..............{x'(t) = Vx = ||V||*2/sqrt(5) = 8/sqrt(5)

    Now to find the components of the acceleration

    y'(x) = 2/y
    y'(t) = (2/y)(x'(t))

    y"(t) = 2*[(-1/y^2)*(y'(t))*(x'(t)) + (1/y)(x"(t))]

    here is where im stuck

    1 equation 2 unknows and i'm having trouble coming up with another independent equation for either

    y"(t) or x"(t)

    does anyone see something about the acceleration that could help me out?
  2. Joined
    02 Mar '06
    Moves
    17881
    22 Jan '10 08:24
    well you can probably make your life a little easier by using y^2 = 2x to see that y = (2x)^1/2

    so y'(t) = 2/y * (x'(t))= 2/(2x)^1/2 * (8/sqrt(5))= 8/5*sqrt(10)*x^(-1/2) -- note i hate doing algebra in text i have no idea if i messed up that simplification

    now y''(t) = [(-1/2)*(8/5)*(sqrt(10))x^(-3/2)] * x'(t)??? ... though this is why i ALSO hate prime notation: i'm taking t-partials in an equation with x's so do we need the chain rule there?

    if this is accurate y''(t) = [(-1/2)*(8/5)*(sqrt(10))x^(-3/2)] * 8/sqrt(5) = -64/10*sqrt(2) * x^(-3/2)
  3. Standard memberTheMaster37
    Kupikupopo!
    Out of my mind
    Joined
    25 Oct '02
    Moves
    20443
    22 Jan '10 08:58
    Originally posted by Aetherael
    well you can probably make your life a little easier by using y^2 = 2x to see that y = (2x)^1/2

    so y'(t) = 2/y * (x'(t))= 2/(2x)^1/2 * (8/sqrt(5))= 8/5*sqrt(10)*x^(-1/2) -- note i hate doing algebra in text i have no idea if i messed up that simplification

    now y''(t) = [(-1/2)*(8/5)*(sqrt(10))x^(-3/2)] * x'(t)??? ... though this is why i ALSO hat ...[text shortened]... rate y''(t) = [(-1/2)*(8/5)*(sqrt(10))x^(-3/2)] * 8/sqrt(5) = -64/10*sqrt(2) * x^(-3/2)
    Why so difficult?

    If y^2 = 4x

    Then y = -2*sqrt(x) or y = 2*sqrt(x)

    Then y'= -1/sqrt(x) or y'= 1/sqrt(x)

    Then y'' = 1/2x*sqrt(x) or y'' = -1/2x*sqrt(x)
  4. Subscriberjoe shmo
    Strange Egg
    podunk, PA
    Joined
    10 Dec '06
    Moves
    7733
    22 Jan '10 13:36
    Originally posted by Aetherael
    well you can probably make your life a little easier by using y^2 = 2x to see that y = (2x)^1/2

    so y'(t) = 2/y * (x'(t))= 2/(2x)^1/2 * (8/sqrt(5))= 8/5*sqrt(10)*x^(-1/2) -- note i hate doing algebra in text i have no idea if i messed up that simplification

    now y''(t) = [(-1/2)*(8/5)*(sqrt(10))x^(-3/2)] * x'(t)??? ... though this is why i ALSO hat ...[text shortened]... rate y''(t) = [(-1/2)*(8/5)*(sqrt(10))x^(-3/2)] * 8/sqrt(5) = -64/10*sqrt(2) * x^(-3/2)
    Yeah, the chain/product rule is required, and unfortunatley that is not the given solution. the given is

    Ax = .32(m/s^2)
    Ay = -.64(m/s^2)

    So how to get there? haha😕🙂
  5. Standard memberwolfgang59
    howling mad
    In the den
    Joined
    09 Jun '07
    Moves
    45641
    22 Jan '10 16:32
    Originally posted by joe shmo
    hello all, stuck on a problem looking for some insight

    A particle travels along the path, y^2 = 4x with a constant speed of V = 4(m/s). determine the x, and y components of the particles velocity and acceleration when the particle is at x = 4(m)

    im going to use prime notation for ease of formatting

    heres where im at so far

    a particles velocity ...[text shortened]... x"(t)

    does anyone see something about the acceleration that could help me out?
    Pushed for time but my initial thought is to explicitly find the x component of acceleration to get x''(t) .. just as you did for y''(t).

    That should give you second equation.
  6. Joined
    02 Mar '06
    Moves
    17881
    22 Jan '10 17:522 edits
    Originally posted by TheMaster37
    Why so difficult?

    If y^2 = 4x

    Then y = -2*sqrt(x) or y = 2*sqrt(x)

    Then y'= -1/sqrt(x) or y'= 1/sqrt(x)

    Then y'' = 1/2x*sqrt(x) or y'' = -1/2x*sqrt(x)
    but your y' and y'' here are dy/dx and dy^2/d^2x which are derivatives of y with respect to x... but the problem isn't concerned with that relationship so much as how each y and x are changing with respect to a time parameter. maybe only implicitly (in discussion of velocity and acceleration) but still since we need acceleration and velocity x-partials and y-partials i thought it might be useful.

    that being said, your method is probably useful for finding the TOTAL acceleration, and then finding which parts of it are in which directions using the formulas joe used in his post above to find the Vx and Vy
  7. Joined
    02 Mar '06
    Moves
    17881
    22 Jan '10 18:06
    Originally posted by Aetherael
    well you can probably make your life a little easier by using y^2 = 2x to see that y = (2x)^1/2

    so y'(t) = 2/y * (x'(t))= 2/(2x)^1/2 * (8/sqrt(5))= 8/5*sqrt(10)*x^(-1/2) -- note i hate doing algebra in text i have no idea if i messed up that simplification

    now y''(t) = [(-1/2)*(8/5)*(sqrt(10))x^(-3/2)] * x'(t)??? ... though this is why i ALSO hat ...[text shortened]... rate y''(t) = [(-1/2)*(8/5)*(sqrt(10))x^(-3/2)] * 8/sqrt(5) = -64/10*sqrt(2) * x^(-3/2)
    i think this mostly went to hell when i used the wrong initial equation y^2 = 2x haha
  8. Subscriberjoe shmo
    Strange Egg
    podunk, PA
    Joined
    10 Dec '06
    Moves
    7733
    22 Jan '10 21:23
    Originally posted by Aetherael
    i think this mostly went to hell when i used the wrong initial equation y^2 = 2x haha
    Fret no more, I figured it out my other piece of information.

    It turns out that since the velocity is constant that the sum of the accelerations in the direction of V must be zero

    letting B be the angle between V and the x axis

    Ax cos(B) = Ax:V (the component of the acceleration in the direction of V)
    Ay sin(B) = Ay:V

    Ax*2/sqrt(5) + Ay*1/sqrt(5) = 0

    x"(t) = -y"(t)*1/2

    sub it in and solve...
  9. Subscriberjoe shmo
    Strange Egg
    podunk, PA
    Joined
    10 Dec '06
    Moves
    7733
    22 Jan '10 23:09
    Originally posted by wolfgang59
    Pushed for time but my initial thought is to explicitly find the x component of acceleration to get x''(t) .. just as you did for y''(t).

    That should give you second equation.
    Just out of cuiosity how would you approach that, because I tried to solve for x"(t) explicitly, but substitution yielded division by 0. There is a possibility I could have done it wrong, but maybe you have a different perspective? Since the cat is caught, I just want to see if there is more than one way to skin it so to speak.....🙂
  10. Standard memberwolfgang59
    howling mad
    In the den
    Joined
    09 Jun '07
    Moves
    45641
    23 Jan '10 10:38
    Originally posted by joe shmo
    Just out of cuiosity how would you approach that, because I tried to solve for x"(t) explicitly, but substitution yielded division by 0. There is a possibility I could have done it wrong, but maybe you have a different perspective? Since the cat is caught, I just want to see if there is more than one way to skin it so to speak.....🙂
    Work in Progress ... long time since I did any calculus!!!!!
  11. Joined
    26 Apr '03
    Moves
    25805
    07 Mar '10 22:144 edits
    Here's my working:

    y^2 = 4x
    so: y = 2sqrt(x)
    differentiating
    dy/dx = 1/sqrt(x)
    rearranging we get dy = dx/sqrt(x)

    similarly, we can write the first equation as:
    x = y^2/4
    and differentiate to get
    dx/dy = y/2
    which rearranges to
    dx = y.dy/2

    we know speed is 4 m/s
    i.e. sqrt((dx/dt)^2 + (dy/dt)^2) = 4
    squaring both sides: (dx/dt)^2 + (dy/dt)^2 = 16
    substituting in the expression we got for dy:
    (dx/dt)^2 + (dx/dt)^2/x = 16
    ((x - 1)/x)(dx/dt)^2 = 16
    dx/dt = 4x/(1-x) {equation a}

    using the quotient rule to differentiate equation a
    ddx/dt^2 =4/(1-x)^2 {equation b}

    going back to the equation:
    (dx/dt)^2 + (dy/dt)^2 = 16

    substituting in the equation we got for dx:
    y^2.(dy/dt)^2/4 + (dy/dt)^2 = 16

    5y^2/4(dy/dt)^2 = 16
    (dy/dt)^2 = 4*16.y^(-2)/5
    dy/dt = 8/(sqrt(5)y) {equation c}

    differentiatng that
    ddy/dt^2 = -8/(sqrt(5)y^2) {equation d}

    and we get the necessary answers at {x= 4, y=4} by substituting those values into equations a,b,c and d

    x = 4, y=4
    dx/dt = -16/3
    ddx/dt^2 = 4/9

    dy/dt = 2/sqrt(5)
    ddy/dt^2 = -1/(2*sqrt(5))

    Hmm, I think I made a mistake somewhere, but tired now, going to bed and checking it over tomorrow!
  12. Subscriberjoe shmo
    Strange Egg
    podunk, PA
    Joined
    10 Dec '06
    Moves
    7733
    08 Mar '10 03:46
    Originally posted by iamatiger
    Here's my working:

    y^2 = 4x
    so: y = 2sqrt(x)
    differentiating
    dy/dx = 1/sqrt(x)
    rearranging we get dy = dx/sqrt(x)

    similarly, we can write the first equation as:
    x = y^2/4
    and differentiate to get
    dx/dy = y/2
    which rearranges to
    dx = y.dy/2

    we know speed is 4 m/s
    i.e. sqrt((dx/dt)^2 + (dy/dt)^2) = 4
    squaring both sides: (dx/dt)^2 + (dy/d ...[text shortened]... I think I made a mistake somewhere, but tired now, going to bed and checking it over tomorrow!
    in your equation "a"

    You just slipped up on the algebra

    should be

    (dx/dt)^2 + (1/x)(dx/dt)^2 =16

    (dx/dt)^2(1+x) = 16x

    dx/dt = 4* sqrt(x/(1+x))

    but other than that, thats the alternative I was looking for.

    Thanks
  13. Joined
    26 Apr '03
    Moves
    25805
    08 Mar '10 08:202 edits
    Originally posted by joe shmo
    in your equation "a"

    You just slipped up on the algebra

    should be

    (dx/dt)^2 + (1/x)(dx/dt)^2 =16

    (dx/dt)^2(1+x) = 16x

    dx/dt = 4* sqrt(x/(1+x))

    but other than that, thats the alternative I was looking for.

    Thanks
    Ah, thanks for that Joe.
    I think the long form of writing differentiation as dx/dy helps, because the dx etc can be used as normal variables and rearranged. I don't find the x'' notation very helpful usually. I'm still worried about my calculation though because the speed at that point doesn't seem to come out as 4 🙁
  14. Subscriberjoe shmo
    Strange Egg
    podunk, PA
    Joined
    10 Dec '06
    Moves
    7733
    08 Mar '10 14:39
    Originally posted by iamatiger
    Ah, thanks for that Joe.
    I think the long form of writing differentiation as dx/dy helps, because the dx etc can be used as normal variables and rearranged. I don't find the x'' notation very helpful usually. I'm still worried about my calculation though because the speed at that point doesn't seem to come out as 4 🙁
    Just a slip in equation c

    1/4*y^2*(dy/dt)^2 + (dy/dt)^2 =16

    (dy/dt)^2*(1/4*y^2 + 1) = 16

    dy/dt = 8/sqrt(y^2 +4)

    rough night?🙂
Back to Top